Síntese de Benzimidazóis a partir da Condensação do Citronelal e outros aldeídos com 1,2-fenilenodiamino, utilizando SiO2/ZnCl2 e em Meio Livre de Solvente - Dutra, Luiz Gustavo (2009)
This work was the study of condensation between Citronellal and 1,2-phenylenediamine in presence of SiO2/ZnCl2 (25%) and solvent-free environment. The reaction was carried out at room temperature, under conventional heating and irradiation of a domestic microwave oven and using scientific (Diagram 1). In all cases, it was possible to observe the formation of 2 - [(R) -2,6-dimetileptil-5-enyl]-1-[(R)-3,7-dimetiloctil-6-enyl]-1H-benz[d]imidazole by cyclization of the intermediate diimino generated in situ. The methodology was extended to other aldehydes, which allowed the taking of several benzimidazoles 1,2-dissubstituides with incomes ranging between 65 and 92%.